2021
DOI: 10.3390/antibiotics10040343
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Multidrug Resistant Escherichia coli in Raw Meat and Cloaca Swabs in Poultry Processed in Slaughter Slabs in Dar es Salaam, Tanzania

Abstract: This cross-sectional study was conducted between January and June 2020, in five large poultry slaughter slabs in Dar es Salaam, Tanzania. Purposive sampling was used to select broilers and spent layers, from which meat and cloaca swabs were collected to determine the occurrence of multidrug resistant (MDR) Escherichia coli. Identification of isolates was done using API 20E, and antimicrobial susceptibility testing was performed as per CLSI (2018) guidelines. EBSL (CTX-M, TEM, SHV) and plasmid mediated quinolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
1
15
2
Order By: Relevance
“…In this study, the prevalence of ESBL producing E.coli (2.3%) % is lower than the study finding in South Korea 20% [29] and in Tanzania 4.7% [30]. In addition to the above methodological differences, the observed differences might be also related to the abuse of third generation cephalosporins in food animals, because the use of these antibiotics is greatly linked to the recent emergence of ESBLs-producing bacteria.…”
Section: Plos Onecontrasting
confidence: 75%
“…In this study, the prevalence of ESBL producing E.coli (2.3%) % is lower than the study finding in South Korea 20% [29] and in Tanzania 4.7% [30]. In addition to the above methodological differences, the observed differences might be also related to the abuse of third generation cephalosporins in food animals, because the use of these antibiotics is greatly linked to the recent emergence of ESBLs-producing bacteria.…”
Section: Plos Onecontrasting
confidence: 75%
“…Our previous findings from the study area that compared genotypic and phenotypic results of MDR E. coli isolates, ESBL producers and quinolone resistance found that 80% of the isolates harboured blaCTX-M, 15% aac(6)-lb-cr, 10% qnrB and 5% qepA. None harboured TEM, SHV, qnrA, qnrS, qnrC, or qnrD [46,52]. The ESBL level found in this study was higher than that reported in soil and water samples in Tunisia and DRC Congo [36,41] and lower than previous findings from Tanzania and in Angola [8,53].…”
Section: Discussionmentioning
confidence: 88%
“…We observed that 78.8% of all isolates were MDR E. coli , and that chicken (27.7%) and human (30.3%) isolates had significantly higher MDR isolates as compared to those recovered from rodents (10.8%) and soil (10.0%). Higher occurrence rates of MDR isolates in chickens and humans can be influenced by the frequent use and misuse of antibiotics in humans and poultry in Karatu [ 21 , 22 , 24 , 25 ]. The presence of MDR E. coli isolates in rodents indicates their potential role as hosts or vectors that can spread MDR E. coli to humans and chickens in Karatu and corresponds with other studies in Kenya, Germany, Canada and Vietnam [ 14 , 26 , 27 , 28 ] that associated rodents with carriage and spread of MDR and virulent E. coli strains in communities.…”
Section: Discussionmentioning
confidence: 99%